Pengaruh Social Media Marketing, Perceived Value, Perceived Quality, Brand Image, dan Customer Satisfaction Terhadap Niat Berkunjung Kembali Di AADK Coffee & Eatery Tlogomas Malang - Febrianti, Dini Chusnul; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The expansion of the coffee shop industry in Malang City has intensified competition, compelling business owners to refine their marketing strategies and improve service quality. This study has purposed explore the determinations of social media marketing, perceived value, perceived quality, brand image, and customer satisfaction on revisit intentions at AADK Coffee & Eatery Tlogomas Malang. A quantitative approach rooted in positivist philosophy was employed. The population for this research includes customers who have visited AADK Coffee & Eatery Tlogomas at least once. The sample size of 95 respondents was determined using Malhotra’s formula and purposive sampling, a technique within non-probability sampling methods. Data were collected through interviews, questionnaires, and observations. Data analysis involved instrument tests (validity and reliability), normality tests, classical assumption tests (multicollinearity and heteroscedasticity), multiple regression analysis, hypothesis testing (t-tests for partial effects), and coefficient of determination (R²). The study found that social media marketing and perceived value do not significantly affect revisit intention. However, perceived quality, brand image, and customer satisfaction have significant impacts on revisit intention. This indicates that while social media marketing and perceived value are less influential, factors like perceived quality, brand image, and customer satisfaction are crucial in influencing customers' decisions to return. Keywords: Social Media Marketing, Perceived Value, Perceived Quality, Brand Image, Customer Satisfaction, Revisit Intention.